2017
DOI: 10.1021/acssuschemeng.7b02049
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Nitrogen- and Phosphorus-Codoped Graphene: An Outstanding Support for Pd Catalysts to Oxidize 5-Hydroxymethylfurfural into 2,5-Furandicarboxylic Acid

Abstract: The oxidation of 5-hydroxylmethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) is a sustainable and promising route to bioderived aromatic polyesters. So far, the design of catalyst has been restricted by the unclear working mechanism, and thus most of the supported noble metal catalysts cannot provide a remarkable reaction rate under atmospheric pressures and room temperature. Here we report a new mechanistic insight into the structure–performance correlation of graphene-supported Pd catalysts. It is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…In addition, heterogeneous metal catalysts have been applied in HMF oxidation. Especially supported noble metals like Pt [22][23][24] or Pd [25][26][27] are catalytically active in this reaction. Among others, supported gold-based catalysts show high activity in the oxidation of HMF with oxygen to FDCA [28][29][30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…In addition, heterogeneous metal catalysts have been applied in HMF oxidation. Especially supported noble metals like Pt [22][23][24] or Pd [25][26][27] are catalytically active in this reaction. Among others, supported gold-based catalysts show high activity in the oxidation of HMF with oxygen to FDCA [28][29][30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…The introduction of a small amount (~0.2%) of phosphorous in P-PS-CNF and P-LHT-CNF slightly increased the activity of Au-Pt catalysts compared with undoped Au/PS-CNF and Au-Pt/LHT-CNF ( Table 3). The higher P content in P-HHT-CNF (1.19%) has a higher impact on the activity of Au-Pt (368 h −1 and 185 h −1 , for Au-Pt/P-HHT-CNF and Au-Pt/HHT-CNF, respectively) with almost full conversion and 96% of selectivity to FDCA after only 1 h. The beneficial effect of P cannot be attributed to possible changes in Au-Pt aggregation state, as the nanoparticle size is similar to Au-Pt/HHT-CNF (4.5 and 3.9 nm for Au-Pt/HHT-CNF and Au-Pt/P-HHT-CNF, respectively), but rather to the capability of P to modify the electronic properties of the metal active sites, as already envisaged in previous studies for Pd [26][27][28].…”
Section: Resultsmentioning
confidence: 66%
“…This evidence could be related to the interaction between Au-Pt NPs and P functionalities of the support. Chen et al [28] reported that Pd 2+ species are stabilized by P functionalities in Pd NPs deposited on highly porous phosphorus-doped graphene sheet. The Pd 2+ species are involved in accelerating the oxidation of hydroxyl group of HFCA into aldehyde group of 5-formyl-2-furancarboxylic acid (FFCA), which is the rate-determining step in FDCA production from HMF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations